Peran pengasuhan ayah terhadap sikap positif dalam memandang pernikahan pada perempuan lajang dewasa awal - Aisya Noor Fadilla Putri; Muhammad Salis Yuniardi; Silfiasari (Universitas Muhammadiyah Malang, 2026)
An individual's attitude towards marriage is important because it influences various aspects of life, such as happiness, life satisfaction, and psychological well-being. This attitude is not formed suddenly, but is influenced by various factors, one of which is the role of father's caregiving. This study aims to determine the role of father's caregiving on positive attitudes towards marriage in single women in early adulthood. This study uses a quantitative approach with a correlational design. The criteria for this research subject are single women in early adulthood who have a father or experience being cared for by a father. The sample in this study amounted to 225 respondents using a purposive sampling technique. The instruments used in this study were the Nurturance Fathering Scale (NFS) and Marital Attitudes Scale (MAS). The results of a simple linear regression analysis test indicate that there is an influence of the role of father's caregiving on positive attitudes towards marriage in single women in early adulthood with a probability value of p = <.001 (p <0.05). The implications of this study emphasize the importance of father's involvement in raising daughters as a factor in forming positive attitudes towards marriage in early adulthood.